Badanie skuteczności programu komputerowego do nauki czytania - Jelinek, Jan Amos (Nauczyciel wczesnej edukacji kreatorem środowiska edukacyjnego dziecka, 2016)
Increasing the skills of reading using a computer has been recognized as attractive, both among students and teachers from longer time. The problem is that the effectiveness of these computer programs was determined on the basis of the discussion on evaluation criteria. Typically, to evaluate the effectiveness of educational programs were made on the basis of the opinion of the structure of the program by a specialist, or compare the results of tests examining students’ reading skills. In the article the study included an additional element, regarded by the author as the most important – how the computer program was used by students. The study takes into account this element which indicates that learning at the computer is not as effective as expected.